Neutrosophic AT-ideals of AT-algebra with Applications - Nada Hadi Malik; Zainab Redha Zainy; Qasim Ali Shakir (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
This work introduces the concept of neutrosophic AT-ideals in AT-algebra and presents some associated facts and theorems. The homomorphism of neutrosophic AT-ideals in AT-algebra is examined, and some findings pertaining to them under homomorphism are derived.